Public finance in theory and practice - Musgrave, Richard A.; Musgrave, Peggy B. (New York : McGraw-Hill Book Co., 1989)
The book emphases on public finance distribution function, similar to that on social goods. It theoretically gives an a analysis of fiscal issues
Includes bibliographical references and index.
sju 24/01/2019
Loans
Keywords: Finance, Public